Environmental Principles. From Political Slogans to Legal Rules (2020) – a review of the monograph by Nicolas de Sadeleer - Przybojewska, Ilona (The Opole Studies in Administration and Law, 2023)
The subject of this article is a review of the second edition of the monograph by N. de Sadeleer entitled Environmental Principles. From Political Slogans to Legal Rules, devoted to the principles of environmental protection, in which the Author explains the place and role of the three principles of his choice - the "polluter pays" principle, the precautionary principle and the precautionary principle - in environmental law at all levels (i.e. international, EU and national), taking into account the ongoing evolution of functions and legal status of these principles in the transition between modern and postmodern legal models, taking into account the changing models of thinking about the environment. The aforementioned monograph has the value of a comprehensive and extremely interesting study of the issues of three principles crucial to environmental law, in theoretical and practical dimensions.